Zhodnocení technologií pro využití biomasy - Zahálka, Jiří (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2010)
Bakalářská práce se zabývá technologiemi pro využití biomasy, nabízí jejich souhrn, popis a využití. Další body jsou zaměřeny na zdroje biomasy, ekologické dopady spojené s jejím pěstováním a následným zpracováním. Na závěr práce je zhodnocena ekonomická stránka a legislativa.

The bachelors thesis deals with biomass utilizations technologies, it presents their summary, descriptions and utilization. Other parts concentrated on biomass sources, ecological impact connected with biomass cultivation and its subsequent processing. Economic point of view and legislation are evaluated at the end of thesis.
Evaluation of technology for the biomass incineration.
Keywords: Biomasa; plodiny; odpady; spalování biomasy; chemické procesy; biologické procesy; emise; legislativa; Biomass; crop; waste; biomass combustion; chemical processes; biological processes; emissions; legislation